Empowering Lekki–Ajah Communities: A Hybrid Blueprint for Flood Resilience - Olawale, Olaniran Saheed (Journal of Regional Economics and Development, 2025)
Lagos State's rapid urbanization and climate variability have exacerbated flood hazards, notably in the Lekki-Ajah corridor, where drainage deficits, governance failures, and informal settlement expansion combined to create this recurring crisis. Employing a secondary mixed-methods approach, this policy analysis combines descriptive statistical evaluation of rainfall and flood incidence records with a systematic content review of institutional policies and documented community responses to evaluate contemporary flood governance challenges in the corridor. Six alternative interventions, including structural drainage upgrades, community-based early warning, green infrastructure, regulatory enforcement, institutional coordination, and digital governance, were evaluated using a weighted multi-criteria framework and SWOT analysis. According to the findings, community-based and green infrastructure solutions perform best in terms of equity, feasibility, and sustainability, while digital governance tools enhance transparency and long-term compliance. A recommended hybrid resilience strategy combines targeted drainage upgrades, participatory micro-infrastructure and alert systems, ecosystem restoration, and digital monitoring to maximize each option's capabilities. A pilot implementation in Lekki-Ajah, Oworonshoki, Surulere, Ijora-Badia, and Ajegunle is proposed, with a strong implementation timeframe, financing model (₦20 billion), and monitoring and evaluation framework. This integrated roadmap, drawing on Bardach's Eightfold Path, prioritizes community empowerment, inter-agency collaboration, and adaptive policy-making to provide a scalable paradigm for flood resilience across Lagos' most susceptible corridors.